Digital Governance and Electronic Waste Management at Federal University of Mato Grosso do Sul – Brazil - Joao Vitor Costa; Luciana Montera; Luciano Gonda; Leonardo Chaves de Carvalho; Marcelo Augusto Santos Turine; Camila Celeste Brandao Ferreira Itavo (Journal of Sustainability Perspectives, 2024)
The Federal University of Mato Grosso do Sul (UFMS) has the Information and Communication Technology Master Plan (PDTIC) to guide and monitor the performance of the Information Technology (IT) area within the institution. The IT area at UFMS has the Digital Governance Committee (CGD), responsible for drafting the Information Security Policy (PSI); the Information and Communication Technology Procurement Plan (PCTIC); the Open Data Plan (PDA); and the University's PDTIC. In addition to the Information and Communication Technology Agency (AGETIC), which is responsible for coordinating, guiding, supervising, executing, and controlling the organization's IT activities. This work aims to demonstrate that sustainability is part of both Digital Governance and the curriculum of UFMS students, focusing on the management of Waste from Electrical and Electronic Equipment (WEEE) within the University. The UFMS Solid Waste and Health Services Management Plan (PGRS/PGRSS) outlines guidelines for the management of these materials, and annually, since 2017, the Faculty of Computing (FACOM) at UFMS organizes the Electronic Waste Collection Week, a project aimed at raising awareness among the academic community about disposal, reuse, and recycling, helping to conserve the environment. This action assists in the education of these students by making them protagonists in this initiative. In each edition hundreds of electronic devices have been reused by students and community, serving as an example of socio-environmental impact action. The methodology employed by UFMS to organize and advance electronic waste management efforts involved the establishment of digital governance regulations, along with sustainability management and governance practices, in order to structure and promote electronic waste management actions at UFMS.